Role of sodium during formation of edema in children with nephrotic syndrome - Gurgoze, Metin Kaya; Gunduz, Zubeyde; Poyrazoglu, Muammer Hakan; Dursun, Ismail; Uzum, Kazim; Dusunsel, Ruhan (Wiley, 2011)
Background: The pathogenesis of edema in nephrotic syndrome is not entirely understood. The aim of this study was to contribute to the discussion on edema pathogenesis in nephrotic syndrome by following changes in volume and sodium retention for the course of the disease in children with steroid-sensitive nephrotic syndrome (SSNS). Methods: Forty-one children with SSNS were included in the study. The patients were divided into three groups (group I: relapse-edematous; group II: relapse-edema free; group III: remission). We investigated the value of the significance and area of sodium retention and vasoactive hormones. In addition, we measured parameters such as inferior vena cava collapsibility index, left atrium diameter, and total body water (TBW) to determine the volume load and cause of edema in children with SSNS. Results: TBW increased in the relapse-nephrotic syndrome group and the difference was statistically significant among groups (P < 0.001). However, inferior vena cava collapsibility index and left atrium diameter were not different among groups. Fractional sodium excretion was lower in children with relapse nephrotic syndrome (P < 0.05). Conclusion: Although TBW increases in children with SSNS, intravascular volume is normal. In addition, hypoalbuminemia and sodium retention of the proximal tubule cause edema in children with SSNS.
Keywords: children; edema; nephrotic syndrome; sodium